MODERN MANAGEMENT TRENDS:THE COMPETENCE OF THE COMPANY’S PERSONNEL - ZAMLYNSKYI, Andrii; LEBEDEVA, Inna; GORYN, Marta (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article discusses one of the main areas in personnel management. The essence of this area is to manage the process of determining, applying, evaluating, acquiring, stimulating and developing the competencies of employees. Some authors understand as competence the formally described requirements for the personal, professional and other qualities of employees of an enterprise. In this understanding, competencies are used in evaluating personnel. Therefore, in the process of managing the enterprise’s personnel, it becomes necessary to determine the competencies of candidates for vacancies during the initial interview and hiring, to analyze and predict the possibility of their acquisition and further development by employees to meet the needs of the enterprise in personnel of the appropriate level. Some companies use only key competencies, others develop and use only managerial competencies to evaluate top managers, and some companies develop only special (technical) competencies for job groups of various departments, and only a small number of companies pay attention to personal competencies. The construction of a competency system for each position in the enterprise is considered as a tool used at all levels of work with personnel. The first and main direction, the definition of competencies necessary for the enterprise and the creation of a system of special competencies necessary for employees of the enterprise. The competency model is a complete set of competencies and behavioral indicators necessary for an employee to successfully perform his functions, manifested in relevant situations and time, for a particular enterprise with its special and individual goals, and corporate culture. A relevant direction of further research is the development and justification of the expediency of using fundamentally new motivational and communication levers and models during and after military aggression as a system for countering risks and force majeure circumstances and forming a new paradigm of sustainable development management.